Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd003979.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Rehabilitation after surgery for flexor tendon injuries in the hand

Abstract: Controlled mobilisation regimens are widely employed in rehabilitation after flexor tendon repair in the hand. This review found insufficient evidence from randomised controlled trials to define the best mobilisation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 29 publications
0
23
0
4
Order By: Relevance
“…In light of this body of research, Kim et al () suggested the following surgical techniques to improve upon historical methods: (1) 8‐core suture strands with a high‐caliber suture material, (2) a purchase length of ∼1.2 cm, (3) a locking‐loop configuration with the knot placed outside the repair site, and (4) a peripheral suture placed deep into the tendon and far away from the cut end. An equally extensive series of studies examining rehabilitation protocols for flexor tendon repairs also exists (Small et al, ; Thien et al, ; Chesney et al, ). Both early active motion protocols and regimens combining passive flexion with active extension result in low rates of tendon re‐rupture and good range of motion following repair.…”
Section: Current Clinical Treatments For Common Tendon Injuriesmentioning
confidence: 99%
“…In light of this body of research, Kim et al () suggested the following surgical techniques to improve upon historical methods: (1) 8‐core suture strands with a high‐caliber suture material, (2) a purchase length of ∼1.2 cm, (3) a locking‐loop configuration with the knot placed outside the repair site, and (4) a peripheral suture placed deep into the tendon and far away from the cut end. An equally extensive series of studies examining rehabilitation protocols for flexor tendon repairs also exists (Small et al, ; Thien et al, ; Chesney et al, ). Both early active motion protocols and regimens combining passive flexion with active extension result in low rates of tendon re‐rupture and good range of motion following repair.…”
Section: Current Clinical Treatments For Common Tendon Injuriesmentioning
confidence: 99%
“…There is controversy regarding certain rehabilitation issues such as early/late mobilisation, position and type of the splint and mobilisation protocols (controlled passive motion, active extension/passive flexion or controlled active motion). There is still insufficient evidence to define the best mobilization strategy 44. Experimental studies suggest that motion enhances tendon repair especially the strength of repair by reducing oedema and preventing adhesions 45.…”
Section: Acute Flexor Tendon Injuriesmentioning
confidence: 99%
“…All these studies except one (Peck et al, 1998) suggest better results with the EAM protocol. However, the clinical evidence supporting superiority of EAM in contrast to CPM is insufficient; not even systematic reviews could conclude what was the best rehabilitation protocol (Thien et al, 2004, Chesney et al, 2011.…”
Section: Rehabilitationmentioning
confidence: 99%